Electrostatic fields for the control of evaporating charged fuel sprays. (March 2023) - Fredrich, Daniel; Weiand, Erik; Giusti, Andrea
Abstract: The current socio-economic shift towards electrification of the transport sector and development of hybrid thermal–electric propulsion systems provides new opportunities for the development of 'clean' aviation technologies. In this work, the use of electrostatic fields to control the location of electrically charged fuel droplets is proposed as a novel technology to enhance pre-evaporation of liquid sprays in confined spaces. An electrospray in cross-flow is numerically investigated using large-eddy simulations for a range of flow and droplet conditions in order to study the feasibility of the approach. A deterministic model is further introduced to compute the trajectory of single droplets in a steady cross-flow. This enables a separation of the effects of turbulence, droplet repulsion and evaporation through comparison with data obtained from the large-eddy simulations, and at the same time provides a cheap computational tool to explore a wider range of operating conditions. It is shown that external electrostatic fields below the breakdown threshold of air can significantly change the trajectory of charged droplets at moderate flow velocities. Moreover, electrostatic forces acting in the opposite direction of the mean cross-flow can potentially be used to stabilise the spray position within a confined region, hence allowing for an increase of the residence time available for full evaporation. The application and modulation of such electrostatic forces is envisioned as a new paradigm to achieve ' targeted evaporation ' in next-generation hybrid thermal–electric aero-engines and to improve the fuel-oxidiser mixing quality. The electrical power associated with the external electrostatic field to achieve droplet stabilisation is negligible compared to the thermal power released by complete combustion of the injected fuel. In addition, it is shown that stabilisation of the droplets enhances the evaporation rate (by more than 30%) and mixing quality due to an increase of the relative velocity between the droplets and the gas flow, as well as the turbulence induced by the stagnating spray cloud. The results of this work offer new insights for the development of advanced fuel injection strategies based on electrohydrodynamics. Highlights: Electrostatic forces are applied to control the trajectory of charged fuel sprays. Droplets can be stabilised in a bulk flow to achieve quasi-infinite residence times. Such stabilisation was found to increase the evaporation rate by more than 30%. The proposed concept can also enhance the fuel-oxidiser mixing quality.